Investigating the risk of international construction projects using artificial-fuzzy neural networks technique - Kermanimoghaddam, Ali (Technium Sustainability, 2023)
The purpose of implementing the risk management process is to identify and root the causes of each risk, analyze it, plan response methods and assign risks to appropriate factors, in order to effectively control the preferred risks. This article aims to analyze risk management in construction projects using fuzzy artificial neural networks in the form of a descriptive-survey study and in the category of applied research. Data analysis was done using MATLAB software using MATLAB software to ensure the soundness of the method and to implement project risk management in international construction projects, and the results indicate success in terms of risk.